The prevalence of transfusion transmitted infections in ABO blood groups and Rh type system - Jitendra Singh Nigam; Savitri Singh; Viplesh Kaur; Sumit Giri; Ravi Prakash Kaushal (Hematology Reports, 2014)
Screening of blood and blood products is important to reduce the risk of transfusion transmitted infections (TTIs). The transfusion of unscreened or inadequately screened blood and blood products are the major source of TTIs. The aim of this paper is to find out the prevalence of TTIs in ABO blood groups and Rh type system. A total of 4128 blood donors were screened from January 2010 to April 2014. Serological tests were performed for hepatitis B surface antigen (HBsAg), anti hepatitis C virus (Anti-HCV), anti HIV-1 and 2, venereal disease research laboratory test (VDRL) and malaria parasite (MP) antigen. In seroreactive donors, HBsAg, Anti-HCV, VDRL, MP antigen and anti HIV were positive in 40 cases, 26 cases, 19 cases, 6 cases and 2 cases, respectively. Highest percentage of HBsAg, Anti HCV, VDRL, MP antigen and anti HIV was observed in blood group A negative (2/50), O negative (1/66), B negative (1/91), AB positive (2/377) blood group respectively. In the present study, the total number of Rh-negative donors is lower when compared to Rh-positive blood donors, but Rh-negative blood donors show higher percentages of seroreactivity for TTIs. Larger scale studies at molecular level are required to improve the knowledge of this aspect.